2002
DOI: 10.1210/en.143.6.2376
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Selective Peroxisome Proliferator-Activated Receptor- 2 Ligands on Adipocyte Versus Osteoblast Differentiation

Abstract: PPAR gamma is activated by diverse ligands and regulates the differentiation of many cell types. Based on evidence that activation of PPAR gamma 2 by rosiglitazone stimulates adipogenesis and inhibits osteoblastogenesis in U-33/gamma 2 cells, a model mesenchymal progenitor of adipocytes and osteoblasts, we postulated that the increase in marrow fat and the decrease in osteoblast number that occur during aging are due to increased PPAR gamma 2 activation. Here, we show that the naturally occurring PPAR gamma li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
263
2
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(279 citation statements)
references
References 0 publications
6
263
2
8
Order By: Relevance
“…However, only a few studies on the effect of PPARs acting specifically via fatty acids in osteoblast maturation are available at this point in time. In an excellent study, Lecka-Czernik et al [144] …”
Section: Fatty Acids Ppars and Bone Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few studies on the effect of PPARs acting specifically via fatty acids in osteoblast maturation are available at this point in time. In an excellent study, Lecka-Czernik et al [144] …”
Section: Fatty Acids Ppars and Bone Physiologymentioning
confidence: 99%
“…In addition, the LA peroxidation products 9, 10-epoxyoctadecenoic acid (9,10 EOA), 9,10 dihydroxyoctadecenoic acid (9,10DHOA) and 9-hydroxyoctadecadienoic acid (9-HODE) have also been reported to be ligands for PPARγ2 [144]. Still et al [147] have reported action of LA on bone via binding to PPARα/δ.…”
Section: Fatty Acids Ppars and Bone Physiologymentioning
confidence: 99%
“…That can be reasonably explained as follows. Lecka-Czernik et al 40 and Ali et al 41 reported the effect of ppar-gamma expression on adipocyte versus osteoblast differentiation. They showed evidence that the activation of ppar-gamma2 stimulates adipogenesis and inhibits osteoblastogenesis in mesenchymal progenitor cells.…”
Section: Gene Expression Analysis Of Major Lineage-defining Factors Imentioning
confidence: 99%
“…24,25,27 Figure 3. Photomicrograph of mineralized nodules after 14 days of exposure to polyunsaturated fatty acids.…”
Section: Oil Red O Staining Versus Alkaline Phosphatase Activity As Mmentioning
confidence: 99%
“…23 These receptors are activated by free fatty acids and their oxidation products as well as by some prostaglandins derived from fatty acids that induce the differentiation of preadipocytes into adipocytic cells. [24][25][26][27] AA, which is a precursor for prostaglandins of the -2-family, has specifically been implicated in adipocyte differentiation. 23 With ageing there is a decrease in osteoprogenitor cells with an accompanying increase in adipocytes in bone marrow.…”
Section: Introductionmentioning
confidence: 99%